RNA polymerases and associated factors. - Adhya, Sankar Lal; Garges, Susan (Methods in enzymology, 2003)
RNA polymerase is molecule important to gene transcription. Along with associated factors, RNA polymerase is part of the process in which RNA is transcribed to produce a protein. * Construction and purification of RNA polymerases * DNA microarrays and bacterial gene expression * Functional analysis of transcription factors.